2002
DOI: 10.1007/s00467-002-0955-6
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 produces no renal vasoconstriction in conscious newborn lambs

Abstract: Experiments were carried out to investigate the effects of endothelin-1 (ET-1) on renal vascular tone during development under physiological conditions in conscious lambs. Renal blood flow (RBF), renal vascular resistance (RVR), mean arterial pressure (MAP), and heart rate (HR) were measured in conscious, chronically instrumented lambs aged approximately 1 week and 6 weeks before and after intra-arterial (i.a.) injection of 0, 100, 200, and 400 ng/kg body weight of ET-1. In addition, plasma levels of ET-1 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It was concluded that ET-1 is a renal vasodilator in the near-term fetal sheep, resulting from activation of ET B receptors presumably through production of NO. Our previous studies in conscious newborn lambs have also shown that ET-1 administration elicits no renal vasoconstriction [6]. In fact, a renal vasodilation is seen-albeit transiently-after ET-1 injection in 1-weekold lambs (see also Fig.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…It was concluded that ET-1 is a renal vasodilator in the near-term fetal sheep, resulting from activation of ET B receptors presumably through production of NO. Our previous studies in conscious newborn lambs have also shown that ET-1 administration elicits no renal vasoconstriction [6]. In fact, a renal vasodilation is seen-albeit transiently-after ET-1 injection in 1-weekold lambs (see also Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Measurements were continued for 5 min before and 20 min after close arterial injection of 100 ng/kg of ET-1. The dose of ET-1 was selected from previous dose-response studies [6] as the EC 50 RBF response to ET-1. The dose of l-NAME was selected from previous dose-response studies [13,15] as that required to inhibit intrarenal arterial NO production for a minimum of 60 min in conscious lambs aged 1-6 weeks of postnatal life.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery was performed using aseptic techniques, as previously described [29,37]. Briefly, anaesthesia was induced with a mask and isoflurane (∼5%) in oxygen, the trachea was intubated and anaesthesia was maintained by ventilating the lungs with isoflurane (1.5-2.5%) in a 3:2 mixture of nitrous oxide and oxygen.…”
Section: Surgical Proceduresmentioning
confidence: 99%